Flexibility for runners - Jenkins, J.; Beazell, J. (Clinics in Sports Medicine, 2010)
Flexibility training, commonly referred to as stretching, has become a standard part of athletic training for nearly all sports. Athletes almost universally engage in some form of flexibility training because of the perception that it prevents injury and may enhance sports performance. With specific regard to running, controversy has arisen regarding these proposed benefits of stretching. In this article, the authors seek to define flexibility training and evaluate the evidence for its clinical benefit. They also describe the components of a general lower quarter flexibility program that they encourage their patients to follow at the University of Virginia Runner's Clinic.